Efektifitas Guided Imagery dan Terapi Musik Klasik Mozart terhadap Tingkat Kecemasan Ibu Hamil Trimester III di Puskesmas Penyengat Olak Muaro Jambi - Ika Murtiyarini; Herinawati Herinawati; Ruwayda Ruwayda; Neli Hartati (Universitas Baiturrahim, 2023)
According to WHO, 13% of pregnant women experience anxiety disorders, especially depression. In fact, it could reach 19.8% in developing countries. In Indonesia alone, 28.7% of 373 million pregnant women experience anxiety, and 52.3% of 679,765 occur on the island of Sumatra. Seeing the above phenomena, the purpose of this study was to determine the effectiveness of and Mozart classical music therapy on reducing the anxiety level of third trimester pregnant women at the Penyengat Olak Health Center in 2021. The method in this study is a quasi-experimental method, where measurements were carried out twice using a two-group pretest-posttest design. The population and sample in this study were 60 pregnant women in the third trimester at Penyengat Olak Health Center, Muaro Jambi Regency, using total sampling technique, 30 people in the group and 30 people in the classical Mozart music therapy group who met the inclusion criteria. Data analysis in this study used univariate and bivariate tests. The results of this study indicate that the level of anxiety before being given reached an average of 22.03% and decreased to an average of 17.63% after being given the treatment. Meanwhile, the level of fear before being given Mozart classical music therapy reached an average of 23.07% and decreased to an average of 10.60% after being given Mozart classical music therapy. With the mean rank value in reached 41.93. Meanwhile, Mozart's classical music therapy is 19.07. From the results obtained, it can be said that media is more effective than Mozart classical music therapy media. Thus, media can be used for further intervention for Puskesmas Penyengat Olak